From Cuba to most of the neotropic: habenaria bicornis (orchidaceae) is widespread from Mexico to southeastern Brazil - Batista, João; Proite, Karina; Carvalho, Bruno M; Vale, Aline A; Felix, Leonardo P (Lankesteriana: International Journal on Orchidology, 2014)
Habenaria bicornis was first described in 1835 from Cuba and has only been known from that country and from a few records in Panama from the 1920s. Here we show that H. bicornis and H. goyazensis, known from Brazil and Guyana, are conspecific and that the species is distributed from Mexico to southeastern Brazil. Niche modeling and collection data indicate that this species has a preference for wet lowland savannas and its distribution is predicted to include most of the Neotropics with suitable habitats. The molecular phylogenetic analyses based on DNA sequences from the nuclear internal transcribed spacer (ITS) region and part of the plastid matK gene placed H. bicornis in an isolated position near the base of the Neotropical clade, although with low support. In terms of its morphology, its relationships are likewise not clear as there are no evident similarities between H. bicornis and the basal subclades or any other Neotropical subclade. Cytogenetic analysis indicated a basic chromosome number of x=21, similar to other basal Neotropical species.